Green Techno-Entrepreneurship model on student business performance: The mediating role of competitive advantage - Astri Ayu Purwati; Zulfadli Hamzah; Muhammad Luthfi Hamzah (Cogent Business & Management, 2023)
This study aimed to examine the influence of green techno-entrepreneurship on student business performance, with competitive advantage acting as a mediator. The research focused on university students in Riau Province, Indonesia, who are engaged in entrepreneurial activities. A purposive sampling technique was employed to select a sample of 288 participants. The findings indicate that the Use/Adoption of Environmental Friendly Operations significantly boosts competitive advantage. However, it does not directly exert a significant positive impact on student business performance. In this context, competitive advantage has been validated as an effective mediator between the Use/Adoption of Environmental Friendly Operations and student business performance. Contrarily, Use/Adoption of Technologies in Operations did not significantly affect either competitive advantage or students' business performance. As such, no mediating role for competitive advantage was identified in the relationship between Use/Adoption of Technologies in Operations and business performance. Entrepreneurial competency positively and significantly influenced both student competitive advantage and business performance. Furthermore, this study found that having a robust competitive edge also significantly enhances student business performance. Therefore, entrepreneurial competency affects business performance through its impact on competitive advantage. Students possessing high levels of entrepreneurial competence are likely to achieve substantial competitive advantages which subsequently yield positive effects on their businesses' performances.
Keywords: 650; competitive advantage; entrepreneurial competency; student business performance; Use/adoption of environmental friendly operations; Use/adoption of technologies in operations